The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s11094-022-02548-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Safety of Dihydroquercetin (Review)

Abstract: Dihydroquercetin (DHQ) is a bioflavonoid with high antioxidant, capillary-protective, and anti-inflammatory activity. DHQ has previously been used for treating Middle East respiratory syndrome coronavirus (MERS-CoV) infection and is currently considered a potential regulator of oxidative stress as part of COVID-19 multipurpose therapy. DHQ has a high safety profile but low bioavailability that limits its use. Innovative techniques (liposomization, crystal engineering, etc.) can be used to increase its bioavail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Therefore, new research contents were added to this study. In addition, dihydroquercetin is a flavonoid compound with high antioxidant, capillary-protective, and anti-inflammatory activity [ 23 ]. Some studies have shown that dihydroquercetin was more effective than quercetin in inhibiting the superoxide produced by xanthine oxidase and has a stronger antioxidant effect [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, new research contents were added to this study. In addition, dihydroquercetin is a flavonoid compound with high antioxidant, capillary-protective, and anti-inflammatory activity [ 23 ]. Some studies have shown that dihydroquercetin was more effective than quercetin in inhibiting the superoxide produced by xanthine oxidase and has a stronger antioxidant effect [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, taxifolin shows greater efficacy than green tea polyphenols and may increase the cytotoxicity of chemotherapeutic agents [247]. Taxifolin has a safety profile but low bioavailability [248]. Like other polyphenols, its concentrations and doses used in preclinical models have been significantly higher than those that could be achieved in clinical use.…”
Section: Polyphenolsmentioning
confidence: 99%
“…It has been demonstrated to have various physiological functions and pharmacological activities, such as antioxidant, anti-inflammatory, and anticancer biological activities [10]. It has also been established as a safe food supplement through evaluations of its toxicity [11] and the enhancement of its antioxidant capacity to improve production performance [12]. TA has many promising health-promoting effects.…”
Section: Introductionmentioning
confidence: 99%